Bloqueio Contínuo do Plexo Lombar via Posterior Bilateral com Bomba de Infusão Descartável. Relato de Caso - Imbelloni, Luiz Eduardo [UNESP]; Vieira, Eneida Maria [UNESP]; Devito, Fábio Stuchhi [UNESP]; Ganem, Eliana Marisa [UNESP] (Elsevier, 2011)
Background and objectives: The number of bilateral total hip arthroplasties (THA) has been increasing every year. Postoperative analgesia by continuous perineural infusion of local anesthetic has been shown favorable results when compared to systemic analgesia. The use of elastomeric pumps has increased patient satisfaction when compared to electronic models. The objective of this report was to describe a case of continuous bilateral posterior lumbar plexus block with an elastomeric infusion pump in a patient submitted to bilateral hip arthroplasty. Case report: This is a 46 year-old female patient weighing 65kg, 162cm, with rheumatoid arthritis and hypertension, physical status ASA II, scheduled for bilateral THA in a single stage. She had been on corticosteroids for 13 years. Hemoglobin=10.1g.dL-1, hematocrit=32.7%. Routine monitoring. Spinal anesthesia with 15mg of 0.5% isobaric bupivacaine. General anesthesia with propofol (PFS) and remifentanil, and intubation without neuromuscular blockers. Right THA and, at the end, lumbar plexus block with a stimulator and a set of 150mm needle and injection of 20mL of 0.2% bupivacaine and introduction of a catheter. Left THA and, at the end, the same procedure. Anesthetic dispersion and contrast were investigated. Elastomeric pump was installed with 0.1% bupivacaine (400mL) at a rate of 14mL.h-1. The patient was transferred to the Intensive Care Unit (ICU). After 24 hour, a new pump was installed with the same solution. She did not receive any boluses for 50 hours. After removal of the catheter, pain was controlled with oral ketoprofen and dypirone. Conclusions: Continuous peripheral blockade with infusion of 0.1% bupivacaine with elastomeric pumps is a safe and effective procedure in adults. © 2011 Elsevier Editora Ltda.
Continuous Bilateral Posterior Lumbar Plexus Block with a Disposable Infusion Pump. Case Report
Keywords: Anesthesia, Conduction; Arthroplasty, Replacement, Hip; Bupivacaine; Infusion Pumps; Lumbosacral plexus